Investor Attention, Market Anomalies, and Listing Board Effects: Evidence from Indonesian Technology Stocks - Heraeni Tanuatmodjo; Vena Melliyani; Yusuf Murtadlo; Imas Purnamasari (Yayasan Darussalam Bengkulu, 2026)
Background: The persistent underperformance of Indonesian technology stocks between 2022–2024, marked by the dominance of negative abnormal returns, raises a compelling question about behavioral forces shaping price dynamics that deviate from fundamental values. This study examines the effect of digital investor attention on stock returns with the stock listing board as a moderating variable among technology-sector companies listed on the Indonesia Stock Exchange over 2020–2025. Method: Using purposive sampling, 29 technology firms were selected from 47 listed companies, yielding an unbalanced panel of 1,218 monthly observations. Investor attention was measured via the Search Volume Index (SVI) from Google Trends, while stock return was proxied by abnormal return computed using the Capital Asset Pricing Model. Moderated Regression Analysis was conducted using PROCESS Macro Hayes Model 1 in IBM SPSS Statistics 27. Results: Digital investor attention positively and significantly affects stock returns (β = 0.9610; t = 5.797; p < 0.05). The listing board does not independently affect returns but significantly weakens the investor attention–return relationship (β = −0.2326; t = −4.014; p < 0.05), with the strongest moderation on the Development Board (R² = 9.4%). Conclusion: These findings demonstrate that a stock exchange's board classification architecture shapes the degree to which attention-driven anomalies translate into abnormal returns. This study contributes novel empirical evidence on listing board classification as a moderating variable in the behavioral finance literature.